Carbon stocks and sinks in forestry for the unitéd Kingdom greenhouse gas inventory. COST E21 Workshop. Contribution of forests and forestry to mitigate greenhouse effects. Joensuu (Finland). 28-30 Sep 2000 - Milne R.; Hargreaves K.; Murray M. (Biotechnologie, Agronomie, Société et Environnement, 2000)
Afforestation in the UK has been significant and continuing since 1920 (up to 30,000 ha per year). Planting data is used to drive a dynamic process-based carbon accounting model (C-Flow) to estimate removals of atmospheric CO2 to these forests. It is assumed that the afforestation can be represented by the characteristics of Sitka spruce for conifers and beech for broadleaves. The present area of forest considered for these estimates is 1.6 millions ha. In 1990 the uptake to trees, litter, soil and products was 2.6 terragramme C, rising to 2.8 terragramme C in 1998. Deforestation is believed to be small. Supporting measurements show that the model predicts long term uptake by conifers well but that losses from planted peat shortly after establishment need further consideration. Process modelling of beech growth suggests that it is primarily dependant on atmospheric CO2 concentration and not on stomatal control per se. UK research priorities relevant to preparation of GHG (greenhouse gas) Inventories are presented.